Comparing the impacts of different exercise interventions on patients with type 2 diabetes mellitus: a literature review and meta-analysis - Shuangtao Xing; Yifan Zhang; Yanjiao Chen; Shijie Feng; Yiqing Zhang; Paulo Moreira; Paulo Moreira (Frontiers in Endocrinology)
ObjectiveExercise interventions are a recommended method of diabetes management through which patients can achieve blood glucose control, increase muscle volume, and improve insulin sensitivity, while also improving blood lipids, blood pressure, and cardiovascular health. A few studies on the effects of physical exercise on diabetic patients have been published in recent years. This article focuses on exploring evidence on which exercise interventions generate which effects in diabetic patients, namely, high-intensity interval training (HIIT), method training (MT), aerobic exercise training (AET), resistance training (RT), and combined training (CBT).MethodsRandomized controlled trials (RCTs) that focused on the effects of exercise interventions on blood glucose and blood lipids of patients with type 2 diabetes mellitus were reviewed. A network meta-analysis was performed to compare the effects of the five exercise interventions in diabetic patients, namely the impacts on glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). The study was strictly conducted following the PRISMA Protocol, and the Cochrane Risk of Bias Assessment Tool 2.0 was used to objectively evaluate the risk of bias in the implementation of the study.ResultsThis review included 25 RCTs in total, with 1,711 subjects. Meta-analysis suggests that, compared with conventional therapeutic treatment, exercise interventions can reduce blood glucose indexes, namely HbA1c, FBG, TC, TG, HDL, and LDL. RT and AET have been shown to reduce TC; HIIT, MT, AET, and CBT have been shown to improve HDL; and HIIT, MT, AET, and CBT have been shown to improve HDL. The MT and RT exercise types can reduce LDL. Evidence also suggests that MT can lower HbA1c, TG, and LDL levels, and RT lowers cholesterol levels. HIIT exercise appears to improve FBG and HDL levels.ConclusionThe five types of exercise generate different effects on the key clinical dimensions of diabetes. MT seems to be the optimal choice to improve HbA1c, TG levels, and LDL, while HIIT improves FBG and HDL levels, whereas RT exercise appears to be the optimal exercise to lower cholesterol levels.